2019
DOI: 10.1103/physrevb.100.195428
|View full text |Cite
|
Sign up to set email alerts
|

Emission of plasmons by drifting Dirac electrons: A hallmark of hydrodynamic transport

Abstract: Direct current in clean semiconductors and metals was recently shown to obey the laws of hydrodynamics in a broad range of temperatures and sample dimensions. However, the determination of frequency window for hydrodynamic phenomena remains challenging. Here, we reveal a phenomenon being a hallmark of high-frequency hydrodynamic transport, the Cerenkov emission of plasmons by drifting Dirac electrons. The effect appears in hydrodynamic regime only due to reduction of plasmon velocity by electron-electron colli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 48 publications
(72 reference statements)
0
21
0
4
Order By: Relevance
“…(For a discussion of crossover from the hydrodynamic to the ballistic regime and of the Cherenkov instability in graphene, see Refs. [38,39].) The suggested mechanism should work for any electronic spectrum, but calculations are more compact and physically transparent for parabolic spectrum characterized by the effective mass m. We thus restrict ourselves to the discussion of this case only.…”
Section: Energy Dissipation and Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…(For a discussion of crossover from the hydrodynamic to the ballistic regime and of the Cherenkov instability in graphene, see Refs. [38,39].) The suggested mechanism should work for any electronic spectrum, but calculations are more compact and physically transparent for parabolic spectrum characterized by the effective mass m. We thus restrict ourselves to the discussion of this case only.…”
Section: Energy Dissipation and Amplificationmentioning
confidence: 99%
“…Recently, some theoretical and experimental studies of grating-gate graphene structures utilizing plasma resonances have been reported [38][39][40]. In particular, the electromagnetic simulations of the graphene gratinggate structures [41] show the possibility of the resonant plasmons strongly coupled to THz radiation even at roomtemperature.…”
Section: Introductionmentioning
confidence: 99%
“…Проводимость в виде (8) совпадает с проводимостью из [11] в приближении малых q, которое верно для волн с фазовой скоростью больше скорости Ферми. Формула, аналогичная (8) встречается в работах [4,18].…”
Section: гидродинамическая проводимость графенаunclassified
“…Плазмоны в гидродинамическом режиме могут возбуждаться постоянным током по черенковскому механизму [4], а также трансформироваться в электронно-дырочные звуковые колебания вблизи точки зарядовой нейтральности [5,6]. Скорость таких электронно-дырочных звуковых колебаний в графене определяется выражением ν F / √ 2, где ν F -скорость Ферми в графене [4,7]. При замедлении гидродинамических плазмонов до скоростей, близких к скорости Ферми, в графене может возникать пространственная дисперсия проводимости.…”
Section: Introductionunclassified
See 1 more Smart Citation